Quasi-civilian defence minister and civilian authority: the case study of Indonesia’s Ministry of Defence during Joko Widodo presidency - Haripin, Muhamad (2023)
The President of the Republic of Indonesia, Joko Widodo, appointed two former military generals, Ryamizard Ryacudu (2014–2019) and Prabowo Subianto (2019–present), for the first- and secondterm defence minister positions consecutively. The appointment of military officers – either retired or active – as defence ministers has been perceived as a recipe for potential democratic setbacks. Current studies on the quasi-civilian defence minister mainly focused on explaining the logic behind such appointments. On the other hand, our study attempts to test the argument about whether the decision to select former military figures to lead the Ministry of Defence undermines civilian control. This article examines: (1) the institutional arrangement of the defence establishment; (2) the composition of the Indonesian Ministry of Defence’s leadership structure; and (3) the leadership activities and key initiatives. The findings are that military officers have indeed dominated the ministry’s organisational structure. Nevertheless, such domination did not automatically translate into the deterioration of civilian supremacy as the institutional arrangement limits those quasi-civilian defence ministers’ manoeuvres.